IMPRINTING ZEOLITE-MODIFIED GLASSY CARBON AS A VOLTAMMETRIC SENSOR FOR URIC ACID - Miratul Khasanah; Muji Harsini; Alfa Akustia Widati (Indonesian Journal of Chemistry, 2013)
Development of the uric acid sensor through coating of glassy carbon (GC) electrode with imprinting zeolite (IZ) was carried out. Zeolite was synthesized by mixing TEOS, TBOT, TPAOH, and water followed by hydrothermal process. Zeolite was molded together with uric acid to produce IZ. The deposition potential of IZ and uric acid to the GC surface was -0.6 V during 150 sec with addition of KNO3 0.02 M as supporting electrolyte. The method gives linearity of 0.9834 (concentration 5.6x10-9M - 2.8x10-8 M), precision 1.89 - 7.65%, sensitivity 0.33 µA/nM/cm2, limit of detection 5.9x10-9 M, and accuracy 96.26 ± 0.55% (n = 5). The developed sensor showed a high selectivity toward uric acid. The presence of ascorbic acid, creatine, and creatinine with an equal concentration with uric acid did not interfere on the uric acid analysis.